2019
DOI: 10.1080/17453674.2019.1657342
|View full text |Cite
|
Sign up to set email alerts
|

Use and outcome of 1,220 primary total elbow arthroplasties from the Australian Orthopaedic Association National Joint Arthroplasty Replacement Registry 2008–2018

Abstract: Background and purpose — The Australian Orthopaedic Association National Joint Replacement Registry (AOANJRR) was analyzed to determine trends in use of primary total elbow arthroplasty (TEA), the types of prostheses used, primary diagnoses, reasons for and types of revision, and whether the primary diagnosis or prosthesis design influenced the revision rate.Patients and methods — During 2008–2018, 1,220 primary TEA procedures were reported of which 140 TEAs were revised. Kaplan–Meier estimates of survivorship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…Total elbow arthroplasty (TEA) is an effective treatment choice for patients with severe pain or instability of the elbow or for patients requiring high-quality motion [ 48 ]. However, there is a risk of long-term complications after TEA, such as aseptic loosening, infection, and polyethylene or bushing wear [ 49 ]. Elbow deformity in patients with osteomyelitis variolosa is often combined with distal humeral dysplasia, lengthening of the condyles of the humerus, and distortion of the long bones [ 13 , 25 ], which further increases the operating difficulty of TEA.…”
Section: Discussionmentioning
confidence: 99%
“…Total elbow arthroplasty (TEA) is an effective treatment choice for patients with severe pain or instability of the elbow or for patients requiring high-quality motion [ 48 ]. However, there is a risk of long-term complications after TEA, such as aseptic loosening, infection, and polyethylene or bushing wear [ 49 ]. Elbow deformity in patients with osteomyelitis variolosa is often combined with distal humeral dysplasia, lengthening of the condyles of the humerus, and distortion of the long bones [ 13 , 25 ], which further increases the operating difficulty of TEA.…”
Section: Discussionmentioning
confidence: 99%
“…In their article published in Acta Orthopaedica in August 2019, Viveen et al reported on 1200 primary total elbow replacements from the Australian Orthopaedic Association National Arthroplasty Replacement Registry (AOANARR) implanted between 2008 and 2018. 13 They observed an almost equal three way split for indication of TEA between trauma, osteoarthritis (OA) and rheumatoid arthritis (RA) overall, but in more recent times (since 2016) trauma and OA are becoming more common whilst RA is decreasing in frequency, likely due to the improved medical management of RA. TEA performed for OA appeared to show a higher revision rate compared to trauma (HR 1.8 95% CI 1.1, 3.0) and RA (HR 2.0 95% CI 1.3, 3.1).…”
Section: Shoulder and Elbowmentioning
confidence: 99%
“…Although an arthroscopic arthroplasty is the preferred choice in terms of surgical possibilities, the symptoms and grade of the OA should be considered. Other surgical options include a debridement only with loose body removal, or total elbow replacement or in severe cases an elbow arthrodesis may be applicable, depending on the patient presentation and activity demands [15]. The patient should be informed about the progression of the OA in general and that the surgery cannot prevent further progression of osteoarthritic changes with time.…”
Section: Indications and Contraindicationsmentioning
confidence: 99%